The Legal and Illegal Use of Force by Prison Officers in Ukraine - Symkovych, Anton (The prison journal, 2019)
Although prison order rarely rests on naked force, its availability defines a prison. A penological truism holds that officers’ deployment of force signals a breakdown in order, not normality. However, is the truism universally valid? Adding evidence from a former Soviet bloc country, the study examines the place of force in officers’ daily work in a men’s medium-security prison in Ukraine. Drawing on a semiethnographic study, the findings show that even though availability of force was central to preventing escapes and securing prisoner compliance, its actual deployment was relatively rare. Officers’ consideration and actual use of both legal and illegal force depended on legal ramifications, the position of the superiors, and prisoner reaction. It also reflected their views on the adequacy of formal penal power and legitimacy of force for corrective purposes.